Grit in College Students: Literature Review - Riza Noviana Khoirunnisa; Nur Eva; Hetti Rahmawati (Jurnal Psikologi Teori dan Terapan, 2023)
Grit is an important aspect of student academic performance. Various studies on grit have been conducted, but no one has examined individual differences in grit among college students. The purpose of this study is to determine individual differences related to grit in college students. The method used is a literature study on research articles published in reputable international journals. A search for reputable international journals in the 2018-2022 range used the Science Direct page, with the keywords grit, individual differences, and motivation. The search returned 10 articles that matched the criteria. The article was then analyzed using a literature review. The results of the study show that individual differences have a relationship with student grit. The implication of this research is to show that accommodating various individual differences in the learning process is very much needed by students. The persistence of effort and consistency of interest which are the dimensions of grit are also influenced by individual differences. Grit has a very important role for students in achieving the goals set. Grit merupakan salah satu aspek penting dalam performa akademik mahasiswa. Beragam kajian mengenai grit telah dilakukan, namun belum ada yang menelaah mengenai perbedaan individu dalam grit di kalangan mahasiswa. Tujuan studi ini untuk mengetahui perbedaan individu yang terkait dengan grit pada mahasiswa. Metode yang digunakan adalah studi literatur pada artikel-artikel hasil penelitian yang dipublikasikan di jurnal internasional bereputasi. Penelusuran jurnal internasional bereputasi pada rentang tahun 2018-2022 menggunakan laman Science Direct, dengan kata kunci grit, perbedaan individu, dan motivasi. Penelusuran menghasilkan 10 artikel yang sesuai dengan kriteria. Artikel kemudian dianlisis menggunakan telaah literatur. Hasil studi menunjukkan bahwa perbedaan individu memiliki hubungan dengan grit pada mahasiswa. Implikasi dari penelitian ini adalah menunjukkan bahwa mengakomodasi berbagai perbedaan individu dalam proses pembelajaran sangat diperlukan mahasiswa. Perseverance of effort dan consistency of interest yang merupakan dimensi dari grit juga dipengaruhi oleh perbedaan individu. Grit memiliki peran yang sangat penting bagi mahasiswa dalam mencapai tujuan yang telah ditetapkan.